FEATURES OF GEOMETRIC PROBLEMS FOR THE DEVELOPMENT OF SELF-AWARENESS AND LOGICAL THINKING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses ways to develop self-awareness and logical thinking through geometric problems.